M-CHOLINOLYTICS IN RHEABILITATION OF CHILDREN WITH VOIDING DISFUNCTION AND URNARY BLADDER HYPERACTIVITY - I.V. Kazanskaya; E.L. Vishnevsky; R.O. Ignatiev; N.B. Guseva ("Paediatrician" Publishers LLC, 2006)
Voiding dysfunction is a common problem in pediatrics. Hyperactive urinary bladder is the most frequent cause of voiding dysfunction. Macholinolytic drugs are the first choice treatment for urinary bladder hyperactivity. The «urination pathology» center has investigated the efficacy of an macholinolytic, oxybutynin. The study included 25 children (aged 6-14) with different causes of voiding dysfunction and bladder hyperactivity. Oxybutynin was administered with a dosage of 5 mg twice a day, the follow up period was 8 weeks. The control evaluation of urodynamics (voiding rhythm, uroflowmetry, residual urine volume) was performed at 4-8 weeks. Symptoms of bladder hyperactivity have been eliminated in 50% of patients, the bladder capacity has increased in 70% of cases, the frequency of night and day incontinence has diminished. The report demonstrates that oxybutynin has been most effective in patients with urinary bladder volume between 80 and 100 ml. the side effects, as dryness of mucous membranes and voiding difficulties, have been rarely observed. These side effects could be avoided by individual dose titration.Key words: voiding dysfunction, urinary bladder hyperactivity, oxybutynin, children.